The Suffixation Processes in the Morphology of Tiv Verbs. Issue 1 (2nd January 2018) - Waya, David; Babarinde, Olusanmi
ABSTRACT: Understanding the suffixation processes of Tiv requires understanding the tonal system, as tones are pivotal to word realisations. This article examines the internal structure of Tiv verbs as well as the suffixation paradigm and the possible phenomenon of tone as a morpheme. The Item-and-Arrangement (IA) and Item-and-Process (IP) models serve as theoretical guides for the analysis of the data. The study observes both regular and irregular patterns in Tiv verb realisations. The substitution of certain segments or modification of tone accounts for the past tense. Meanwhile, to realise aspects, the suffixes -n, -on, -en-, -un or tone are inflected on verb roots. It is also observed that some verbs do not take an overt suffix but a vowel extension to indicate a dynamic imperative formation. It is clear that some affixes perform dual roles in the language. The article recommends further research on how tone and affixes interact in the expression of grammatical categories.